Pest categorisation of Hoplolaimus galeatus - EFSA Panel on Plant Health (PLH); Claude Bragard; Paula Baptista; Elisavet Chatzivassiliou; Francesco Di Serio; Paolo Gonthier; Josep Anton Jaques Miret; Annemarie Fejer Justesen; Alan MacLeod; Christer Sven Magnusson; Panagiotis Milonas; Juan A Navas‐Cortes; et al. (EFSA Journal, 2023)
Abstract The EFSA Panel on Plant Health performed a pest categorisation of Hoplolaimus galeatus (Nematoda: Hoplolaimidae) for the EU. H. galeatus belongs to the order Rhabditida, subfamily Hoplolaiminae. This nematode is not reported from the EU and is not included in the EU Commission Implementing Regulation 2019/2072. It is widely distributed in the USA and is also reported from South America, Africa, Asia and Australia. The identity of H. galeatus is clearly defined and methods for its identification are available. H. galeatus is polyphagous and natural hosts include barley, wheat, rye, red and white clover, alfalfa, cabbage, pine, spruce, oak, apple, grapevine, as well as various ornamental plants and turf grasses. These hosts are grown over vast areas of the EU. The climate of the EU is suitable for the establishment of H. galeatus. Pathways of entry are host plants for planting except seeds, but also soil as a contaminant. Soil import to the EU is prohibited and special requirements apply to import of machinery for agricultural/forestry purposes from third countries. Impact of the nematode is best known for North American plant species. The nematode has been reported to damage cotton, maize, soybean, pine, oak and turfgrass. Many of the hosts represent a considerable economic and environmental value to the EU. Therefore, the Panel concludes that H. galeatus satisfies all the criteria that are within the remit of EFSA to assess for it to be regarded as a potential Union quarantine pest.